“PERLINDUNGAN KONSUMEN TERHADAP PEREDARAN MAKANAN YANG MENGANDUNG PENGAWET BERBAHAYA (STUDI PASAR JUNJUNG BUIH KOTA SINTANG)” - Rini Safarianingsih (Universitas Kapuas Sintang, 2020)
Packaged food is a food product that is widely circulated and free in the community. Foods that will be circulated for consumption so as not to harm consumers must include adequate, correct, honest and responsible information. So that every business actor in the food sector that is circulated is burdened with responsibility, especially if the food he produces causes losses to consumers. Based on the Decree of the Regent of Sintang Number: 510/156 / KEP-INDAGKOP-C/ 2015 dated February 27, 2015, on the Integrated Supervision of Hazardous Materials Abused in Food, a joint team chaired by the Sintang DistrictHealth Office held a raid in the Junjung Buih market and the shops in the Sintang Inpres Market. Related to the raid conducted by this integrated team, where the purpose of the raid is in order to anticipate the entry of hazardous materials to the market, such as borax, formalin, dangerous dyes Keywords: Protection, Consumer, food preservatives